Pengaruh Likuiditas dan Perputaran Persediaan Terhadap Pertumbuhan Laba Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia (BEI) - Risma Aziza; Mursidah Nurfadillah; Praja Hadi Saputra (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
This research investigates how liquidity and inventory turnover affect the growth of profits for companies in the food and beverage industry that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The study employs a quantitative method and applies multiple linear regression to assess the relationship between the independent variables—liquidity (proxied by the current ratio) and inventory turnover—and the dependent variable, namely profit growth. The analysis reveals that liquidity, when examined individually, does not exert a significant impact on profit growth. Conversely, inventory turnover demonstrates a positive and statistically significant relationship. When analyzed jointly, both liquidity and inventory turnover are found to have a significant effect on profit growth, although they collectively account for only 11% of the variation. These results underscore the critical role of operational efficiency, particularly in managing inventory, as a driver of improved financial performance. The outcomes of this research are meant to offer useful information for business practitioners, investors, and scholars involved in strategic planning within the food and beverage industry.